Diagnosis of MV oil filled cable terminations with X-ray imaging and infrared (IR) thermography - Mohd Rafi, Adzman; Ismail, Daut, Prof. Dr.; Muzamir, Isa; Baharuddin, Ismail; Omar, Aliman; Lehtonen, Matti; Hyvonen, Petri (Science Publications, 2011)
Link to publisher's homepage at http://thescipub.com/